Des femmes et des gâteaux - Maria Leticia Mazzucchi Ferreira (Conserveries Mémorielles)
The content of this article is extracted from research about the candies of Pelotas, city of southern Brazil. This research approached the candies as a immaterial heritage.Classified as fine candies and fruit candies (colonial candies), the root of this know-how is in the late 19th century with the daughters of beef jerky producers, at a time of crisis in the saladeril activity.The interviews reveal that the candie makers had a memory linked to the body’s gestures, to the senses, whether through the olfactory memory (the know-how originated from the syrup scent), or through the visual memory (based on how the candy looks, to know if it is good or not).The learning of the candy maker profession is linked to the portuguese cuisine. However, the recipies of Pelotas have also other sources and ways of doing.